Pola Manajemen Lembaga Pengembangan Tilawatil Qur’an (LPTQ) Provinsi Sumatera Utara - Mardian Idris Harahap; Putri Ayunda Br. Limbong; Friska Fauziah (ISLAMIKA, 2023)
The Tilawatil Quran Development Institute (LPTQ) is a place for qori and qori'ah to learn, explore, and improve their abilities, including the ability to read the Koran, practice tahfizh, and carry out other activities. So a management pattern is needed that must be carried out by LPTQ of North Sumatra Province in order to carry out MTQ activities optimally through the management function. The research method used is a qualitative descriptive form approach which was carried out from 18 November 2022 to 02 December 2022 at the office of the North Sumatra Tilawatil Qur'an Monitoring Institute (LPTQ). The pattern of management that is carried out, namely planning (Planning) by carrying out long and short term programs. Organizing by preparing groupings and regulations to be used during activities, Actuating by using leaders who are sent as guides and directors for coaches, and trainers in training participants to the fullest in participating in National competitions, Controlling by carrying out evaluation of the results achieved by contest participants at the national level in order to provide improvements for the future and also provide maximum preparation.